Sick leave and professional assistance for multiple sclerosis individuals in Vä sterbotten C ounty, northern Sweden - Sundström, P; Nyström, L; Svenningsson, A; Forsgren, L (Multiple Sclerosis Journal, 2003)
The aims of this study of a cross-sectional multiple sclerosis (MS) population in V ä sterbotten C ounty, northern Sweden, were to estimate the prevalence of sick leave, professional assistance and housing; to study risk factors for sick leave; and to estimate the odds for sick leave in comparison with the general population of the county. The consequences of MS-related incapacity on the socioeconomic factors studied were considerable. A lmost half (45%) of prevalent MS cases aged 18-64 years were fully sick listed and only one-third (35%) were not sick listed at all. Every fourth individual in the prevalence population received professional assistance, and 9% were living in care homes or special apartments for the disabled. Multiple logistic regression analysis identified the Expanded Disability Status Scale (EDSS) as the strongest predicto r of sick leave. The time from symptom onset to full sick leave leading to temporary or permanent disability pension was significantly shorter for cases with progressive onset, higher age at onset and in males. The risk of full sick leave due to MS was six times higher than in the general population.